KAJI TEORITIK ASPEK TERMOHIDROLIK REAKTOR RISET PADA DAYA 2 MW - Reinaldy Nazar; Aryadi Suwono; T.A Fauzi Soelaiman (Mesin, 1998)
The thermohydraulic aspect utilization on a nuclear reactor is very dominant, because the system gives limitation on the reactor operation. Regarding the problem, theoretical analysis of thermohydraulic aspect is done for a research reactor of 2 MW with hexagonal conï¬guration of fuel elements With an assumption that the power generation each fuel element is the same and the other facilities are neglected, the output of FLUENT V4.25 program gave information that theoretically this research reactor can be operated on thermal power of 2 MW.